Design of an IoT-Based Water Level Monitoring System for Flood Detection in Ungaran (Elkom: Jurnal Elektronika dan Komputer, 2026)
Flooding is a frequent natural disaster in Indonesia that significantly impacts the socio-economic conditions of the community. In the West Ungaran area of ​​Semarang Regency specifically in Dliwang Village (RT 06/03) there is a small river prone to overflowing during periods of heavy rainfall. This situation highlights the need for a water level monitoring system capable of automatically, accurately, and continuously detecting potential floods. This study aims to design an Internet of Things (IoT) based flood detection and water level monitoring system using an ESP8266 microcontroller integrated with HC-SR04 ultrasonic and raindrop sensors. The system utilizes a buzzer for early warning alarms and an LED indicator to signal flood alert statuses. Sensor data is transmitted in real-time to the Blynk IoT platform, allowing for monitoring via internet connected devices such as smartphones. The design results demonstrate that the system effectively detects changes in water levels and rainfall conditions, providing rapid alerts when water levels reach specific thresholds. Consequently, this system serves as an effective alternative solution to support flood mitigation efforts in flood prone areas.